Peningkatan Karakter Kedisiplinan Siswa dengan Pembelajaran E-Learning Berbasis Masalah Kearifan Lokal - Matondang, Khoiruddin; Lubis, Ulfa Annisa; Saragih, Risna Mira Bella; Irvan, Irvan; Azis, Zainal; Siswadi, Siswadi (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to analyze the influence of e-learning learning based on local wisdom problems on improving the character of student discipline at Al-Azhar High School Medan. The subject of the study was a student of Al-Azhar High School Medan grade XII. The research method used is descriptive with quantitative and qualitative approaches. Data was collected through questionnaires, observations, interviews, and documentation. The research subjects consisted of grade XII students who were selected purposively, with a total of 146 students. The results of the study show that the application of the e-learning learning model based on local wisdom problems has a positive impact on improving student discipline, especially in the aspects of technology use, ethics and social interaction, as well as involvement in local culture-based learning. The findings indicate that the integration of local cultural values into e-learning not only enriches teaching materials, but also increases students' motivation, responsibility, and independence in managing the learning process. The practical implications of this research can be used as a basis for the development of innovative learning methods that combine technology and local wisdom to improve the quality of character education in the school environment.